FE modelling of ultralight foam-filled structures. (1st January 2002) - Megukd, S.A.; Stranart, J.C.; Heyerman, J.
In this paper, we present a method for modelling the quasi-static collapse of foam-filled ultralight aluminium structures using LS-DYNA. Three aspects of axial crushing of foam-filled structure were examined: the effect of foam density, wall thickness and width of the tube. An increase in the specific energy absorption of up to 37% was observed. An experimental study on the quasi-static crushing of empty and foam-filled box columns was also carried out in order to validate the finite element model.